Aspects of Late Weichselian deglaciation in South Norway: timing of deglaciation, ice sheet geometry, and climate variations inferred from surface exposure ages of Late Pleistocene and Holocene landforms - Marr, Philipp; Winkler, Stefan; Löffler, Jörg (ERDKUNDE, 2019)
The investigation of periglacial and related landforms in South Norway is of great interest for exploring the timing of deglaciation and to assess their geomorphological connectivity to palaeoclimatic changes during the Late Pleistocene and the Holocene. The ice margins of the Scandinavian Ice Sheet during the Last Glacial Maximum (LGM) are reasonably well established. Palaeo-ice thickness can, however, only be estimated by modelling and remains uncertain over large parts of Norway due to sparse field based evidence. Because of the significant influence of the former horizontal and vertical ice-sheet extent on sea-level rise, atmospheric and oceanic circulation patterns, erosive properties of glaciers and ice sheets, englacial thermal boundaries, and deglaciation dynamics, it is crucial to improve the understanding of the topographic properties of the LGM ice sheet. Despite recent progress, there is a lack of terrestrial evidence in the form of numerical age data from South Norway. In this study two high-mountain regions and their surroundings in west (Dalsnibba, 1476 m a.s.l.) and east (Blåhø, 1617 m a.s.l.) South Norway were studied to reconstruct palaeoclimatic conditions and deglaciation patterns. Terrestrial cosmogenic nuclide (10Be) and Schmidt-hammer exposure-age dating (SHD) have been utilized to determine the surface exposure age of glacially transported boulders as well as of boulder-dominated glacial, periglacial, and paraglacial landforms and bedrock outcrops. By developing calibration curves at both study sites for the first time it was possible to obtain landform-age estimates from Schmidt hammer R-(rebound) values. In addition, the formation and stabilization of those landforms and the formative processes have provided indications about the Late Pleistocene and Holocene climate variability and its connectivity to landform development.